Integrative analyses of mRNA and microRNA expression profiles reveal the innate immune mechanism for the resistance to Vibrio parahaemolyticus infection in Epinephelus coioides - Qiao, Xifeng; Lu, Yuyou; Xu, Jiachang; Deng, Niuniu; Lai, Wenjie; Wu, Ziyi; Lin, Haoran; Zhang, Yong; Lu, Danqi (Frontiers in Immunology, 2022)
Vibrio parahaemolyticus, as one of the main pathogens of marine vibriosis, has brought huge losses to aquaculture. However, the interaction mechanism between V. parahaemolyticus and Epinephelus coioides remains unclear. Moreover, there is a lack of comprehensive multi-omics analysis of the immune response of grouper spleen to V. parahaemolyticus. Herein, E. coioides was artificially injected with V. parahaemolyticus, and it was found that the mortality was 16.7% in the early stage of infection, and accompanied by obvious histopathological lesions in the spleen. Furthermore, 1586 differentially expressed genes were screened by mRNA-seq. KEGG analysis showed that genes were significantly enriched in immune-related pathways, Acute-phase immune response, Apoptosis, Complement system and Cytokine-cytokine receptor interaction. As for miRNA-seq analysis, a total of 55 significantly different miRNAs were identified. Further functional annotation analysis indicated that the target genes of differentially expressed miRNAs were enriched in three important pathways (Phosphatidylinositol signaling system, Lysosome and Focal adhesions). Through mRNA-miRNA integrated analysis, 1427 significant miRNA–mRNA pairs were obtained and “p53 signaling pathway”, “Intestinal immune network for IgA production” were considered as two crucial pathways. Finally, miR-144-y, miR-497-x, novel-m0459-5p, miR-7133-y, miR-378-y, novel-m0440-5p and novel-m0084-3p may be as key miRNAs to regulate immune signaling pathways via the miRNA-mRNA interaction network. The above results suggest that the mRNA-miRNA integrated analysis not only sheds new light on the molecular mechanisms underlying the interaction between host and V. parahaemolyticus but provides valuable and new insights into resistance to vibrio infection.